Ecosystem assessment and translating a groundskeeping framework into practice for promoting systemic change in higher education - Montgomery, Beronda L.; Black, Sherilynn J. (Frontiers in Education, 2025)
Many institutions include equity as a stated foundational value of their academic missions but often face significant challenges when initiating practices and policies that are aligned with this goal. We propose that institutions and biomedical research environments require innovative approaches to move systems toward equitable environments. The effective transformation of systems involves steps that include an assessment of the current environment; a clear delineation of institutional goals; commitment of resources, structures of accountability, and recognition and/or rewards; as well as identification of transformative or visionary leaders. In the assessment of current systems with regard to progress toward the establishment and cultivation of systems that promote equity, it is critical to identify and maintain effective current practices and to execute necessary changes by drawing on existing change theories or deploying innovative approaches to institutional transformation. The Groundskeeping theoretical framework aligns well with the goal of creating such systems in that it seeks to dismantle (1) notions of the status quo, (2) faulty notions of unbiased meritocracy, and (3) behaviors that create barriers preventing access and advancement. Instead, Groundskeeping creates permissive environments that advance systems toward sustained equitable outcomes. Here, we present an approach that uses the Groundskeeping framework as one possible means for approaching institutional change by initiating systems-level changes in academic and biomedical environments. We provide a step-by-step roadmap to initiate effective approaches that address structural challenges arising from behaviors perpetuating accepted norms, and we also discuss ways to build capacity among individuals as they assess their environments and foster change in their organizations. Finally, we highlight recent effective national approaches aligned with the Groundskeeping framework that work toward change in institutional environments. Ideally, such approaches could be applied in a variety of organizational settings and will translate across different environments to initiate systemic change.